Toward Adoption User Experience Variables for Solo Software Development in Academic and Industry - Kusuma, Wahyu Andhyka; Jantan, Azrul Hazri; Admodisastro, Novia Indriaty; binti Mohd Norowi, Noris (JOIV : International Journal on Informatics Visualization, 2024)
User experience (UX) is frequently mentioned as a rapidly expanding profession. It generates prospects in almost every industry for individuals with expertise in applying design principles and techniques centered around user needs. Many universities specializing in informatics and computer science have acknowledged this demand by integrating more coursework focused on UX into their educational programs. However, the widespread adoption of agile software development and efficient product design has prompted businesses to seek experienced candidates for UX positions, even at entry level. Consequently, individuals aspiring to work in this position need UX experience before acquiring it. Materials: We conducted a pilot study on 235 respondents who voluntarily participated in the research to examine the effect of UX on students' ability to identify a problem in software requirements. Method: This article evaluates the endeavors of a particular institution to bridge this experience gap. The article offers insights and recommended practices for effectively integrating. This research involved industries from two developed countries and one developing country, as well as implementing these aspects on students at one of the institutions with a General Self Efficacy (GSE) scale. Results: The results show the dominant user experience quality aspects. In addition, we provide recommendations for applying to several courses and competencies to enhance student self-efficacy. Implication for Further Research: In this paper, we used a combination of developing a conceptual framework and identifying the industry. With these two methods, we solve the UX gap between industry and academia from the perspective of the UX attribute. Some standards are commonly used in academics to construct the curriculum for their student.